Spinal Cord Injuries – When Is the Initial Tomography Insufficient? - Rodrigues, Pedro Augusto Sousa; Ghizoni, Enrico; Tedeschi, Helder; Joaquim, Andrei Fernandes (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Introduction Spinal cord injury (SCI) is common in polytrauma patients. The standard exam for the initial evaluation is computed tomography (CT), due to its higher sensitivity and specificity when compared with plain radiographs. However, CT is insufficient for the management of some cases, especially to evaluate ligamentous and spinal cord injuries. The objective of the present study is to describe clinical scenarios in which the CT scan was insufficient to guide the treatment of SCIs.Methods We present the cases of four polytrauma patients with normal CT scans at admission and with unstable or surgically-treated lesions.Discussion The cases reported evidence the need for ongoing neurological surveillance with serial physical examination and magnetic resonance imaging (MRI) in cases of neurological injury not explained by CT or occult instability.Conclusion Computed tomography is not always sufficient to determine the management of SCIs. A comprehensive evaluation of the clinical data, CT findings and, occasionally, MRI findings is crucial in order to choose the best conduct.
Keywords: spinal cord injury; computed tomography; polytrauma; diagnosis